Artificial Intelligence in Parkinson - AlSafran, Dannah; Belhabib, Hind; Bandah, Amjad; AlSafran, Sarah; Homran, Sultanah; Yusuf, Nadia (European Journal of Sustainable Development, 2024)
This study explores whether it would be feasible to introduce an Artificial Intelligence (AI)-based diagnostic tool for Parkinson's Disease (PD) to the United States (U.S.). The product is Saudi Arabian and is intended to reduce resource consumption by improving diagnostic accuracy and efficiency. The U.S. market offers a favorable environment because of its advanced healthcare infrastructure and stable democratic political structure. The analysis looks at the political and economic climate, including government support, market opportunities, regulatory compliance, and the strategic advantages of partnerships with local entities. The study suggests that the AI-based diagnostic tool could revolutionize PD prediction and management, offering significant benefits in terms of healthcare outcomes and cost efficiency. Also, it recommends a strategic entry through local partnerships and adherence to U.S. regulatory frameworks to ensure successful market penetration and long-term success. Keywords: Parkinson